AERATED CONCRETE BLOCKS: MAIN TYPES AND EQUIPMENT - Kiyomov Shavkat Fazliddinovich (Web of Journals Publishing, 2024)
This article provides information about the building material aerated concrete, the main types of aerated concrete products, as well as the technological process of manufacturing aerated concrete and the equipment used.
Keywords: aerated concrete, aerated concrete products, aerated concrete blocks, Portland cement, lime, sand, aluminum powder, gypsum, slag, wood chips, conveyor lines; stationary lines; mini-lines; mobile installations.